Relationships between screen viewing and sleep quality for infants and toddlers in China: A cross-sectional study - Lin, Yumin; Zhang, Xueqin; Huang, Yinying; Jia, Zhiwei; Chen, Jing; Hou, Wanling; Zhao, Lili; Wang, Guiyan; Zhu, Jiemin (Frontiers in Pediatrics, 2022)
Aim Currently young children have more opportunity to access all kinds of media, while their sleep duration has been steadily decreasing. However, little is known about the relationships between screen viewing and sleep quality, and the reasons of screen viewing for children under three years old in China. This study aimed to describe the relationships between screen viewing and sleep quality of infants and toddlers in mainland China. Methods A cross-sectional study was conducted. Eight hundred twenty-seven children were recruited at a health care unit from a university affiliated hospital in China, and the questionnaires were completed by their parents. An extended Brief Infant Sleep Questionnaire and a Screen Viewing Questionnaire were used to collect information on children's sleep quality and screen viewing. Multivariate linear regression models were used to assess the relationships between screen viewing and sleep quality among infants and toddlers, adjusted for sociodemographic variables. Results Of the 827 children, 26.9% of the infants and 61.4% of the toddlers did not comply with the World Health Organization (WHO) guideline on screen time. Even after adjusting for the sociodemographic covariates for both infants and toddlers, negative relationships between screen time and total sleep time (P<0.001), and screen time and nighttime sleep (P<0.001) existed. TV viewing time was negatively related to infants' total sleep time (β=-0.15, P<0.001) and toddlers’ nighttime sleep (β=-0.1, P<0.05). Smartphone viewing time was negatively related to toddlers' total sleep time (β=-0.12, P<0.05) and daytime sleep (β=-0.22, P<0.05). Parents who offered screen media for children when they needed to do house chores were more likely to report that their children had less total sleep time (β=-0.1, P<0.05) and shorter longest sleep episode (β=-0.1, P<0.05). Conclusion: The majority of toddlers did not meet the WHO guidelines on screen time in China. Screen time was negatively related to total sleep time and nighttime sleep among infants and toddlers. Practical strategies, such as education programs on children's screen viewing, more outdoor exercises and indoor parent-child activities, early sleep, restricted use of TVs and smartphones, and screen co-viewing, are needed to improve young children's sleep quality and promote their development.